Von Göttern und Menschen : Beiträge zu Literatur und Geschichte des Alten Orients : Festschrift für Brigitte Groneberg ; herausgegeben von Dahlia Shehata, Frauke Weiershäuser und Kamran V. Zand. - Groneberg, Brigitte.; Shehata, Dahlia.; Weiershäuser, Frauke.; Zand, Kamran V. (Cuneiform Monographs, 2010)
Religions, Literature and Languages of the Ancient Near East have always been the main research interests of Prof. Brigitte Groneberg, and now take centre stage in this volume. Twenty four contributors have participated in composing this book, presenting their research dealing with Mesopotamian religion, Akkadian, Sumerian and Ugaritian literature and grammar as well as Babylonian history. Thereby several hitherto unknown texts are published and discussed here for the first time. This volume delivers new insights to several topics concerning Ancient Near Eastern cultures, being hence an important resource not only for Assyriologists and Sumerologists but for anybody interested in the field of Ancient Near Eastern studies.